Nano Scaled Checkerboards: A Long Range Ordering in NiCoMnAl Magnetic Shape Memory Alloy Thin Films with Martensitic Intercalations - Daniela Ramermann; Andreas Becker; Björn Büker; Andreas Hütten; Inga Ennen (Applied Sciences, 2022)
Magnetic shape memory Heusler alloys, such as NiCoMnAl, are considered as promising candidates for magnetocaloric cooling applications. Grown in thin film systems of adjacent layers with austenite and martensite crystal structures of almost equal thicknesses, a long-range ordering phenomenon in the shape of a 3D checkerboard pattern occurs in NiCoMnAl samples. The crystallographic origin of the pattern is proven by transmission electron microscopy (TEM) techniques. The darker fields of the arrangement consist of martensite nuclei superposed with austenite, while the purely austenite regions appear bright in TEM cross sections. The nucleation process is presumably triggered by inhomogeneous local elastic stray fields of primary martensitic nuclei in the austenite matrix and limited by the thicknesses of the martensite and austenite thin films.